Small Farmers Large Field (SFLF): a synchronized collective action model for improving the livelihood of small farmers in India - Baruah, S.; Mohanty, Samarendu; Rola, A.C. (Springer, 2022)
This study pilots the collective action model “Small Farmers Large Field (SFLF)” to overcome the disadvantages faced by millions of small and marginal farmers due to diseconomies of scale and lack of bargaining power in the supply chain. This model is participatory and fexible and allows small farmers to beneft from achieving economies of scale by organizing themselves into groups and synchronizing and harmonizing selected operations. It was piloted in two villages of Odisha, an eastern Indian state, with 112 farmers (35 females and 77 males). These farmers organized themselves into groups and synchronized their operations such as nursery bed management, transplanting, and harvesting collectively to achieve economies of scale. The SFLF farmers purchased inputs (seed and fertilizer) and sold paddy as a group to increase their bargaining power in price negotiations. The results from this pilot study showed that the participating farmers almost doubled their profts. Apart from the monetary benefts, these farmers saved time in many joint activities, including input (seed and fertilizer) purchase, paddy sale, and nursery bed management. Other important benefts of the harmonization and synchronization of farming operations were social harmony and sustainability of the farming system.